Synthesis of Activated Carbon from Corncob for the removal of Lead (Pb²⁺) ions from Aqueous solution using a packed bed Adsorption Column - Bala I. ABDULKARIM; Yusuf M. BABA; Suleiman I. ENEHE; Kamoru A. SALAM; Umar IDRISS (FUDMA Journal of Engineering and Technology, 2025)
This study synthesized activated carbon from corn cobs, an abundant agricultural waste, for efficient lead (Pb²⁺) removal from water. The corn cobs were washed, dried, crushed, and carbonized at 550°C under nitrogen, followed by chemical activation with potassium hydroxide (KOH) at a 1:2 impregnation ratio. The activated material was dried, washed to pH 5, and sieved to 1–2 mm particles. The derived activated carbon was characterized using Thermogravimetric analysis (TGA), differential thermal analysis (DTA), Fourier transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET) analysis. Proximate analysis of raw corn cobs revealed 9.7% moisture, 2.09% ash, 78.37% volatile matter, and 9.2% fixed carbon. TGA/DTA identified key decomposition stages, with optimal carbon yield at 550°C. FTIR confirmed the presence of functional groups (e.g., hydroxyl, carbonyl) critical for adsorption, while BET analysis indicated a high surface area of 776.98 m²/g. Packed-bed column experiments evaluated the effects of adsorbent dose, pH, initial Pb²⁺ concentration, and contact time. Optimal Pb²⁺ removal occurred at pH 5, an initial concentration of 10 mg/L, an adsorbent dose of 3 g/L, and a contact time of 2 hours. The adsorption process followed the Langmuir isotherm model (R² = 0.9998), suggesting monolayer adsorption, while kinetics adhered to the pseudo-second-order model, indicating chemisorption dominance. The results demonstrate the potential of corn cob-derived activated carbon as a sustainable and effective adsorbent for Pb²⁺ remediation in wastewater.
Keywords: Activated carbon, corncob, equilibrium adsorption, lead (pb2+), packed bed adsorption column.